INDIVIDUAL DIFFERENCES BETWEEN THE INTELLIGENCE AND PERSONALITY OF ISLAMIC EDUCATIONAL PSYCHOLOGICAL PERSPECTIVES - Kameelah Songtaya (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
Both intelligence and personality are the Allah’ (S) grace that the two of them have similarities and differences, which are seen according to Islamic educational psychology. This study aimed to examine the differences between them. This research was a literature review with qualitative design by taking material sources from literature studies in books, theses, journals, and other electronic sources that can be scientifically justified. This research showed that there are similarities and differences between intelligence and personalities according to Islamic educational psychology. Both the meaning and the aspects seem good on them. Among those meanings, there is the word “Aqal” which in the context of intelligence it was used to obtain the acquaintance, while in the context of personality it was used as the base of the attitude. In these aspects, the intelligence and personality have the differences; intellectual intelligence is used to grow the intellectual aspects, intellectual rational personality is used behavioral base, as well as while it appears the differences between spiritual-moral intelligence and idealistic personality, spiritual-moral intelligence is used to apply norms or values and idealistic personality is to love norms or values.